PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) DENGAN MEDIA INTERAKTIF QUIZIZZ UNTUK MENINGKATKAN HASIL BELAJAR PPKn PADA SISWA KELAS IV SD INPRES MARISO 2 - Nur Hikmah; Mutmainnah; Syarifah Aeni Rahman (STKIP Subang, 2024)
This study aims to explore strategies for enhancing the quality of Pancasila Education (PPKn) learning through the application of the cooperative Teams Games Tournament (TGT) model combined with the interactive media Quizizz in the fourth grade at SD Inpres Mariso 2. This innovative approach is designed to transform the teaching and learning process into a more participatory, engaging, and meaningful experience for students. The rese arch employs a Classroom Action Research (CAR) method conducted in two systematic cycles. Each cycle consists of planning, implementation, observation, and reflection phases. The subjects of the study include 30 students, and data collection techniques involve learning outcome tests, activity observations, and in-depth interviews. The results indicate that the applied learning model is effective in improving students' academic achievements. The average score of students significantly increased from 70 in the first cycle to 85 in the second cycle. These findings not only reflect an improvement in academic performance but also enhancements in social interaction, learning motivation, and active student engagement in the learning process. The conclusion of this study emphasizes the importance of using cooperative learning models and digital media in primary education. Therefore, this research concludes that the implementation of the TGT model and interactive media Quizizz is an effective alternative for improving student learning outcomes in the fourth grade.